A resilience framework: Sexual health trajectories of youth with maltreatment histories. Issue 4 (8th August 2018) - Fava, Nicole M.; Bay-Cheng, Laina Y.; Nochajski, Thomas H.; Bowker, Julie C.; Hayes, Timothy
ABSTRACT: There is a wealth of knowledge regarding negative sexual outcomes experienced by youth with childhood maltreatment (CM) histories, yet a dearth of research examines healthy sexual development among these youth. This gap exists despite evidence of resilience highlighting alternative and healthy physical, social, and psychological futures for youth who were abused. This study tested whether trajectories of resilience identified in studies of psychological functioning were applicable to sexual health. Using data from the first four waves of the National Longitudinal Study of Adolescent to Adult Health, latent class growth analysis was conducted among individuals with histories of CM ( N  = 1, 437). On average, participants were 15, 16, 21, and 28 years old, respectively, by waves of data collection. About half of the sample was female (55%), the majority were White (66%), and a sizeable portion had experienced multiple forms of CM prior to Wave I (38%). Controlling for CM severity, three distinct sexual health trajectory classes were identified: resilient, survival, and improving, which were differentiated by age and biological sex. Older participants' sexual health was more likely to diminish over time, girls were more likely to show gains in sexual health over time, and significant differences in levels of sexual behaviors between the classes were only present during adolescence. Findings support the need for increased attention on the potential for sexual health despite experiences of CM, and highlight the applicability of resilience theory to youth sexuality.